The Role of Cloud-Native Architecture in Enabling Sustainable Digital Infrastructure - Phanindra Gangina (International Journal of Computational and Experimental Science and Engineering, 2025)
This article examines the critical intersection of cloud architecture and environmental sustainability within enterprise technology solutions. As organizations face increasing pressure to reduce environmental impacts while maintaining competitive digital capabilities, emerging as prominent promoters of cloud-indigenous architectural patterns of resource adaptation. Discussion shows how specific cloud patterns, adaptation tools, and architectural decisions contribute to energy consumption and carbon emissions. Through examination of serverless computing, auto-scaling mechanisms, and robust observability frameworks, the article illuminates pathways through which technical architecture can align with broader sustainability imperatives. Cloud architects occupy a position of significant responsibility in facilitating the transition toward environmentally sustainable digital ecosystems while enabling continued innovation and performance in increasingly complex distributed systems.